Synthetic post-translational modification of histones. (August 2018) - Nadal, Simon; Raj, Ritu; Mohammed, Shabaz; Davis, Benjamin G
Graphical abstract: Highlights: Histones with specific PTMs can be synthesised and assembled in designer nucleosomes. Codon suppression, semisynthesis or chemical mutagenesis allows controlled insertion of PTMs. Designer nucleosomes can probe stability and/or PTM-specific interaction partners. In cellulo techniques show potential for locus-specific incorporation of PTM. Abstract : Chromatin is the physiological template of genetic information in all eukaryotic cells, a highly organised complex of DNA and histone proteins central in regulating gene expression and genome organisation. A multitude of histone post-translational modifications (PTMs) have been discovered, providing a glance into the complex interplay of these epigenetic marks in cellular processes. In the last decade, synthetic and chemical biology techniques have emerged to study these modifications, including genetic code expansion, histone semisynthesis and post-translational chemical mutagenesis. These methods allow for the creation of histones carrying synthetic modifications which can in turn be assembled into designer nucleosomes. Their application in vitro and in vivo is now beginning to have an important impact on chromatin biology. Efforts towards introducing multiple labile modifications in histones as well as expanding their use in cellular biology promise new powerful tools to study epigenetics.